Twin Database of the Secondary School Attached to the Faculty of Education of the University of Tokyo. (23rd December 2019) - Ooki, Syuichi
Abstract: This article profiles the historical twin databases of the secondary education school attached to the Faculty of Education at the University of Tokyo. The school was established in 1948. Every year, about 50 pairs of twins of all sex and zygosity combinations, aged 11–12 years, take an examination, and about 10–20 pairs are admitted based on the results. Three datasets exist: one for applicants (11–12 years old), one for junior and senior high school students (12–18 years old) and one for graduates (18–85 years old). Linking the records from these three databases should facilitate several important research projects, for example, life course genetic epidemiologic studies and the verification of the so-called developmental origins of health and disease hypothesis.